Diabelli Machines8 - Beethoven, Ludwig van 1770-1827; Assis, Paulo de; Michiels, Jan; ME21 Collective (Ghent, Belgium); HERMESensemble (Antwerp, Belgium); Ensemble Interface (Frankfurt am Main, Germany) (Ghent Orpheus Instituut, 2018)
After Ludwig van Beethoven's Diabelli Variations, op. 120CD, DVD and 32-pages booklet.Imagining Beethovens Diabelli Variations as a musical time machine, the Diabelli Machines research project exposes productive tensions between Beethovens own time, its past, and its future. Beethovens original work was composed in two periods: the first draft (1819) included twenty-three variations, while the final version (1823) took the total to thirty-three variations. In the final version, Beethoven included many musical parodies, alluding to Bach, Handel, Mozart, Haydn, and Cramer. Diabelli Machines makes these past references audible to listeners, and adds future compositions, in the form of new pieces reflecting on the Diabelli Variations.Diabelli Machines8 contains a CD, a DVD, and a written essay. The CD presents six new pieces, which were composed in response to specific variations from Beethovens original work, and the first ever recording of the 1819 version of the Diabelli Variations. The DVD documents a live performance of Diabelli Machines in which the time machine is staged through conventional piano performance, transcriptions of the original variations for ensemble, and contemporary pieces. And the comprehensive new essay provides detailed insight into the ideas behind this project and its wider implications for future experimental performance practices of Western notated art music.CD1 Juan Parra Cancino DeleuzApierre 04:29 2 Lucia DErrico Variation 8 05:48 3 Tiziano Manca Parlando 05:34 4 David Gorton [Variation 12] 00:56 5 David Gorton [Variation 13] 01:00 6 David Gorton [Variation 14] 06:00 7 Bart Vanhecke Commentaire . . . Variation 20 05:04 8 Paolo Galli . . . heraus in Luft . . . 04:42 9 Ludwig van Beethoven Diabelli Variations (1819 version) 29:30Ensemble Interface ME21 Collective Paulo de Assis | artistic direction Jan Michiels | fortepianoTotal duration: 63:03Recorded at the Orpheus Institute, Ghent, Belgium, 2022 January 2017 (tracks 18) and 9 December 2017 (track 9). Sound engineer: Juan Parra Cancino.DVD Diabelli Machines4Paulo de Assis | piano and direction HERMESensemble Antwerp ME21 CollectiveTotal duration: 87:00Recorded at De Bijloke, Ghent, Belgium, 9 November 2015. Video recording: Thomas Heiber and Gerhard Schabel. Sound engineer: Juan Parra Cancino. Interviews with: Paulo de Assis, Juan Parra Cancino, Lucia DErrico, Paolo Galli, David Gorton, Tiziano Manca, Bart Vanhecke
Keywords: Beethoven, Ludwig van -- 1770-1827; 19th Century (1801-1900); Composing; Theme and variations; Keyboard music; Piano; Artistic research; Vienna (Austria)